Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jee.20185
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing Graduate Study: Factors Underlying Undergraduate Engineering Students' Decisions

Abstract: Background Enrollment of US students in engineering graduate programs is declining, the proportion of underrepresented groups being even lower at the graduate level than it is at undergraduate levels. Purpose The purpose of this study is to explore engineering undergraduate student perceptions about graduate study, how these perceptions impact their decisions to pursue graduate study, and whether or how these differ by sex and race/ethnicity. Design/Method We administered a survey about graduate study to 1082 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 47 publications
2
45
0
Order By: Relevance
“…A student may be expecting a poor quality of life and, therefore, may never seek out opportunities to socialize or do something they enjoy because they believe they are supposed to be miserable. From the results of Borrego et al [28], we can see that a main motivator for incoming engineering graduate students is their own self-efficacy. While these students have faith in their abilities, when their expectations are not aligned with reality, they may not be as prepared as they believe.…”
Section: Discussionmentioning
confidence: 95%
“…A student may be expecting a poor quality of life and, therefore, may never seek out opportunities to socialize or do something they enjoy because they believe they are supposed to be miserable. From the results of Borrego et al [28], we can see that a main motivator for incoming engineering graduate students is their own self-efficacy. While these students have faith in their abilities, when their expectations are not aligned with reality, they may not be as prepared as they believe.…”
Section: Discussionmentioning
confidence: 95%
“…Extending beyond K-12 and undergraduate engineering studies, a corollary could be made to undergraduate engineers and graduate education. Research has shown that enrollment of US students in engineering graduate programs is declining [6]. Survey data indicate that undergraduates typically hold the preconceived notion that graduate school is simply an extension of their undergraduate degrees except with harder classes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Such exposure can develop the researcher identity similarly to how engineering identity is developed [32]. Further, exposing research experiences to undergraduates can show them the research process and influence their consideration and decision to enroll in graduate school [33].…”
Section: Discussionmentioning
confidence: 99%